Analisis Strategi Guru dalam Meningkatkan Motivasi Belajar Siswa - Amiratul Muzeeb Aditya; Arif Rahman Setyadi; Rizki Leonardho (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2020)
This study aims to understand teacher strategies in increasing student motivation. This research uses qualitative case study research. In this study the researchers collected descriptive data obtained from data collection through observation, interviews and documentation. Analysis of basic teacher skills in implementing thematic learning in elementary thematic learning can be done comprehensively and deeply. In order for students to have high motivation, various efforts need to be made by the teacher to encourage that motivation. Explaining the benefits or objectives of the lesson that students actually receive will encourage student motivation. Everyone suggests something to do. With motivation will grow the urge to do something in his agreement.